A novel Lynch syndrome pedigree bearing germ-line MSH2 missense mutation c.1808A>T (Asp603Val). (11th November 2021) - Sekine, Risako; Shimazu, Kazuhiro; Nakano, Daisuke; Yamaguchi, Tatsuro; Suzuki, Yusato; Fukuda, Koji; Yoshida, Taichi; Taguchi, Daiki; Iijima, Katsunori; Nanjyo, Hiroshi; Shibata, Hiroyuki
Abstract: We report the first pedigree of Lynch syndrome bearing a germ-line MSH2 missense mutation c.1808A>T (Asp603Val). Until now, this missense mutation, in exon 12 of MSH2, was identified as a variant of unknown significance in the International Society for Gastrointestinal Hereditary Tumours database. In vitro induction mutagenesis experiments indicated that the MSH2 mutant protein (Asp603Val) is easily degraded in embryonic stem cells, albeit there is no clinical information concerning this mutant. Our pedigree includes four patients with Lynch syndrome-associated malignancies and clinically matches the Amsterdam II criteria. The proband, a female, first had an endometrial cancer at the age of 49 and then mantle cell lymphoma, colonic and gastric adenocarcinomas and neuroendocrine carcinoma, successively. Her mother also had Lynch syndrome-associated malignancies, including colonic, uterine and gastric cancers, and her elder son had rectal cancer. In the germline of the proband and her son, an MSH2 missense mutation c.1808A>T was discovered. Immunohistochemical analyses indicated that the expression of the MSH2 protein was decreased in the tumors, such as gastric cancer and neuroendocrine carcinoma, due to the missense mutation c.1808A>T. This study showed that the MSH2 missense mutation c.1808A>T (Asp603Val) is a likely pathogenic mutation and is responsible for typical Lynch syndrome-associated malignancies, including neuroendocrine carcinoma. Abstract : A novel germ-line MSH2 missense mutation c.1808A>T (Asp603Val) is identified to be a likely pathogenic mutation of Lynch syndrome. The proband was suffered from colorectal, gastric, endometrial cancers, mantle cell lymphoma and neuroendocrine carcinoma. All of them were treated successfully.